2010
DOI: 10.1177/0091270009360532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High‐Fat Meal on the Pharmacokinetics of Saxagliptin in Healthy Subjects

Abstract: 1211S axagliptin is a potent, selective dipeptidyl peptidase-4 (DPP-4) inhibitor, specifically designed for extended inhibition of the DPP-4 enzyme. DPP-4 is an enzyme that selectively cleaves dipeptides such as the key insulinotropic hormone glucagonlike peptide-1 (GLP-1), converting it from the intact and active form to the inactive form, and is responsible for the short half-life of intact GLP-1 in vivo. 1 Inhibitors of DPP-4 increase levels of endogenous intact GLP-1 and prolong its physiological actions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…In comparison with the fasted state, administration of saxagliptin with a high-fat meal did not affect the C max of saxagliptin, but the median time to reach the C max (t max ) of saxagliptin was prolonged by approximately 0.5 h [31]. After a high-fat meal, the AUC from time zero extrapolated to infinity (AUC ? )…”
Section: Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the fasted state, administration of saxagliptin with a high-fat meal did not affect the C max of saxagliptin, but the median time to reach the C max (t max ) of saxagliptin was prolonged by approximately 0.5 h [31]. After a high-fat meal, the AUC from time zero extrapolated to infinity (AUC ? )…”
Section: Absorptionmentioning
confidence: 99%
“…The somewhat higher AUC value for saxagliptin observed when saxagliptin is taken after a high-fat meal compared with the fasted state is unlikely to result in clinically meaningful alterations in the safety and tolerability profile or the efficacy profile of saxagliptin. Therefore, saxagliptin can be taken without regard to food intake [31].…”
Section: Absorptionmentioning
confidence: 99%
“…62 Ketoconazole is a broad-spectrum antif ungal agent and a potent inhibitor of CYP3A4/5, which might be expected to alter the pharmacokinetics of saxagliptin. 65 Boulton et al 64 concluded that no dosage adjustment would be required when these two drugs are coadministered.…”
Section: Phase 2 Trialsmentioning
confidence: 99%
“…Exposure to 5-hydroxy saxagliptin, however, was reduced by 88%. 26 Based on these findings, reducing the dose of saxagliptin to 2.5 mg once daily for patients who are concomitantly taking ketoconazole or another strong CYP 3A4/5 inhibitor is recommended. 1 Concomitant administration of long-acting diltiazem (360 mg once daily for nine days), a moderate CYP 3A4/5 inhibitor, with a single 10 mg dose of saxagliptin significantly increased the C max and AUC ∞ of saxagliptin by 63% and 109%, respectively, compared with the administration of saxagliptin alone.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%